Constitution is not identity: On equivalence relations in translation of performance and translation for performance - Sarah Maitland (JoSTrans: The Journal of Specialised Translation)
In the race to secure the sub-rights to Amanda Gorman’s ground-breaking performance at the 2021 United States presidential inauguration, a high-profile case emerged in which the translator appointed by Dutch publisher Meulenhoff returned the commission, following criticism of the appointment. Building on the detailed critical interrogations of structural and racial inequity that were published in response to the ensuring controversy, this article delineates additional perspectives, by asking what is instructional in the debate on the who of translating Gorman’s performance, when it comes to other instances of translation of performance, and how we may learn from it in other contexts of translation for performance. Using performance as a concretising lens, or “system of meaning” (Pavis, 1992) that takes on significance only in the coming together of the relationships united in production and reception (p. 25), and through the application of theories of mathematical equivalence relations, this article questions what the controversy tells us about what translation of performance ‘is’ and ‘should’ be, and suggests what lessons might be learned with regard to the notion of equivalence in translation.